Pemanfaatan Limbah Kulit Pisang Kepok (Musa acuminate) sebagai Biosorben Ion Timbal(II) - Gatut Ari Wardani; Winda Trisna Wulandari (Syarif Hidayatullah State Islamic University, 2018)
The use of waste of kepok banana’s peel to adsorb lead(II) metal ion was done. Peel of kepok banana was activated by using nitric acid before used as adsorbent. The optimum time needed by kepok banana’s peel to adsorp lrad(II) metal was 45 minutes with adsorbed metal was 41.779%. Adsorption kinetics of lead(II) at kepok banana’s peel follows kinetic model of Ho pseudo second with the value of R2 is 0.997 and k was 0.063 minutes-1. Isothermal adsorptions from lead(II) on kepok banana’s peel follows Freundlich adsorption model with R2 was 0.893 and capacity of adsorption was 54.752 mg/gram.